Penerapan Strategi It E-Commerce Sebagai Peningkatan Persaingan Bisnis Perusahaan - Triani, Ni Nyoman Alit (AKRUAL: JURNAL AKUNTANSI, 2012)
AbstractThe use of technology e-commerce it on general motors brazilian company can improve revenuenya, company got new consumer, consumers interesting to keep afloat, public service quality and serving consumers indefinitely. By doing payment system three party payment system will be safer than with credit cards. By applying customer relationship management ( crm ) concepts the integration company with customers.